2008
DOI: 10.1021/np800328r
|View full text |Cite
|
Sign up to set email alerts
|

Cycloartane Glycosides from Sutherlandia frutescens

Abstract: Four new cycloartane glycosides, sutherlandiosides A–D (1–4), were isolated from the South African folk medicine Sutherlandia frutescens and their structures established by spectroscopic methods and X-ray crystallography as 1S,3R,24S,25-tetrahydroxy-7S,10S-epoxy-9,10-seco-9,19-cyclolanost-9(11)-ene 25-O-β-d-glucopyranoside (1), 3R,7S,24S,25-tetrahydroxycycloartan-1-one 25-O-β-d-glucopyranoside (2), 3R,24S,25-trihydroxycycloartane-1,11-dione 25-O-β-d-glucopyranoside (3), and 7S,24S,25-trihydroxycycloart-2-en-1-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 21 publications
0
51
0
Order By: Relevance
“…[25][26][27][28][29][30] Although the chemical semi-synthesis of compoundsw ith aC 6 -C 7 -C 6 -C 5 core has been reported, only biocatalysis couldr ealize this reactionu nder mild conditions. [31][32][33] More interestingly,t he biocatalysis of CA by S. racemosum could form 3,10-epoxy (23-26)o r6 ,19-epoxy (27)s tructures, which are reported for the first timef or 9,10-seco-cycloartanes.…”
Section: C-3 or C-6 Acetylation Products 9-12mentioning
confidence: 93%
“…[25][26][27][28][29][30] Although the chemical semi-synthesis of compoundsw ith aC 6 -C 7 -C 6 -C 5 core has been reported, only biocatalysis couldr ealize this reactionu nder mild conditions. [31][32][33] More interestingly,t he biocatalysis of CA by S. racemosum could form 3,10-epoxy (23-26)o r6 ,19-epoxy (27)s tructures, which are reported for the first timef or 9,10-seco-cycloartanes.…”
Section: C-3 or C-6 Acetylation Products 9-12mentioning
confidence: 93%
“…Extracts are also reported to inhibit the action of HIV target enzymes (Hartnett et al 2005). Furthermore, aqueous extracts of field leaves have been shown to contain L-canavanine, gamma amino butyric acid (GABA), D-pinitol, flavonoids and saponins (Fu et al 2008;van Wyk and Albrecht 2008), but reports on their yields in seeds and in vitro cultures are lacking. The objective of this study was therefore to quantify the content of L-canavanine, arginine, GABA and D-pinitol, in seeds, field leaves and in vitro leaves of L. frutescens using modern analytical techniques such as gas and liquid chromatography (Cheng et al 2007;Dias et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The above information implied that compound 1 might possess a 9,10-seco-cycloartane triterpenoid skeleton. [11][12][13] Acid hydrolysis of 1 produced a triterpenoid aglycone (1a), and D-glucose, D-xylose, L-arabinose and D-glucuronic acid as sugar residues which were identified by comparison with the respective authentic samples by GC analysis. The 1 Hand 13 C-NMR spectra of 1a confirmed that the structure of the aglycone moiety (1a) was the same as secomacrogenin B 13) (Table 1).…”
Section: Resultsmentioning
confidence: 99%